Modified Round Robin Algorithm for Resource Allocation in Cloud Computing - Pradhan, Pandaba; Behera, Prafulla Ku; Ray, B.N.B. (Procedia computer science, 2016)
Cloud computing is an attractive computing model since it allows for the provision of resources on-demand. Cloud computing has emerged as a new technology that has got huge potentials in enterprises and markets. Clouds can make it possible to access applications and associated data from anywhere. Companies are able to rent resources from cloud for storage and other computational purposes so that their infrastructure cost can be reduced significantly. Hence there is no need for getting licenses for individual products. Cloud Computing offers an interesting solution for software development and access of content with transparency of the underlying infrastructure locality. The Cloud infrastructure is usually composed of several data centers and consumers have access to only a slice of the computational power over a scalable network. The provision of these computational resources is controlled by a provider, and resources are allocated in an elastic way, according to consumers’ needs. However one of the major pitfalls in cloud computing is related to optimizing the resources being allocated. The other challenges of resource allocation are meeting customer demands and application requirements. In this paper, modified round robin resource allocation algorithm is proposed to satisfy customer demands by reducing the waiting time.